Development of an ocean wave energy harvester with a built‐in frequency conversion function. (16th August 2017) - Viet, N.V.; Wang, Q.; Carpinteri, A.
Summary: The research develops a novel harvester associated with a built‐in frequency conversion device to harness energy from ocean waves based on the piezoelectric effect. The developed harvester consists of 2 generators driven by rotational motions converted from vertical motions by a rack and pinion actuator. The generator has a rotator with a magnetic bar attached to its blade tips and a stator. By this innovative design, the harvester is capable of converting ocean waves with low frequencies to mechanical vibrations with higher excitation frequencies of the piezoelectric transducer for increasing its energy conversion efficiency. A corresponding mathematical model for the harvester is developed to evaluate the generated power. The simulation results show that the generated power increases with increases in the ocean wave height, number of magnetic bars and decreases in the wave period, the distance between 2 opposite magnetic bars, and harvester's submerged part height. The power output is realized up to 260 W with the height, length, and width of the harvester being 1 m  × 1 m  × 1 m, at the ocean wave height and period being 2 m and 7 seconds, respectively. Abstract : This work proposes a novel, optimal, economic, and practical design of ocean wave energy harvester based on piezoelectric effect associating with a frequency conversion function. Corresponding mathematical model is developed to describe the mechanism of wave‐structure interaction and energy harvesting process. A high electric power up to 260 W generated by the proposed harvester is shown.